2022
DOI: 10.3390/membranes12090846
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Groups of Dicationic Pyrazinoporphyrins Regulate Lipid Membrane Binding

Abstract: Photodynamic therapy (PDT) is a widely used technique for skin cancer treatment and antimicrobial therapy. An improvement in PDT efficiency requires not only an increase in quantum yield of photosensitizer (PS) molecules but also their applicability for biological systems. Recently, we demonstrated that the activity of porphyrin-based PSs in the lipid membrane environment depends on the nature of the cation in the macrocycle due to its interactions with the lipid phosphate moiety, as well as the orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We have suggested a model describing the effect of PS location in the membrane on its ability to generate singlet oxygen. The approach we have utilized to study the binding of PS to biological membranes is in vitro modeling of photodynamic processes using model bilayer lipid membranes (BLM) ( Konstantinova et al, 2018 ; Sokolov et al, 2018 ; Jiménez-Munguía et al, 2019 ; Polivanovskaia et al, 2022 ). Simultaneously, we have demonstrated that cationic phosphorus(V) porphyrins possess remarkable photophysical properties including efficient generation of singlet oxygen in water that can be tuned by the varying nature of axial ligands ( Meshkov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have suggested a model describing the effect of PS location in the membrane on its ability to generate singlet oxygen. The approach we have utilized to study the binding of PS to biological membranes is in vitro modeling of photodynamic processes using model bilayer lipid membranes (BLM) ( Konstantinova et al, 2018 ; Sokolov et al, 2018 ; Jiménez-Munguía et al, 2019 ; Polivanovskaia et al, 2022 ). Simultaneously, we have demonstrated that cationic phosphorus(V) porphyrins possess remarkable photophysical properties including efficient generation of singlet oxygen in water that can be tuned by the varying nature of axial ligands ( Meshkov et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…16 In turn, it allows tuning of the physicalchemical properties of the obtained compounds in a range from their solubility in organic or aqueous medium to the enhancement of photophysical outcome. 15,[17][18][19] Formation of metal complexes is an additional degree of freedom in the modification of the electronic structure of porphyrins and thus their characteristics. The presence of a metal center may drastically alter their photophysical, e.g.…”
Section: Introductionmentioning
confidence: 99%